2019
DOI: 10.3390/geosciences9060261
|View full text |Cite
|
Sign up to set email alerts
|

Variability and Trends in Dust Storm Frequency on Decadal Timescales: Climatic Drivers and Human Impacts

Abstract: Dust storms present numerous hazards to human society and are particularly significant to people living in the Dust Belt which stretches from the Sahara across the Middle East to northeast Asia. This paper presents a review of dust storm variability and trends in frequency on decadal timescales from three Dust Belt settlements with long-term (>50 years) meteorological records: Nouakchott, Mauritania; Zabol, Iran, and Minqin, China. The inhabitants of each of these settlements have experienced a decline in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(41 citation statements)
references
References 75 publications
2
39
0
Order By: Relevance
“…The area of Karkheh basin covers 4262000 hectares and covers parts of Khuzestan, Ilam, Hamedan, Lorestan, Markazi, Kurdistan and Kermanshah provinces. The most important tributaries of Karkheh River are: Gamasiab, Qarasu, Seymareh and Kashkan, which are divided into four sub-basins by the name of these four rivers [14] .…”
Section: Geographical Location and Characteristics Of The Study Areamentioning
confidence: 99%
“…The area of Karkheh basin covers 4262000 hectares and covers parts of Khuzestan, Ilam, Hamedan, Lorestan, Markazi, Kurdistan and Kermanshah provinces. The most important tributaries of Karkheh River are: Gamasiab, Qarasu, Seymareh and Kashkan, which are divided into four sub-basins by the name of these four rivers [14] .…”
Section: Geographical Location and Characteristics Of The Study Areamentioning
confidence: 99%
“…Dust activity has a significant impact on the environment and human health (e.g., Lin, Levy, Lei, & Bell, 2012), particularly in the "Dust Belt" that stretches from the Sahara across the Middle East to northeastern Asia (Middleton, 2019). Over the Middle East, dust emissions and concentrations have increased by 15% in the last decade (Yu, Kalashnikova, Garay, Lee, & Notaro, 2018), and it has been found that the formation of dust storms in the Middle East is influenced by both thermal and dynamic processes in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Observations have shown a high frequency of dust storms in the western and southeastern parts of Iran (e.g., Cao, Liu, Wang, Yang, & Luo, 2015;Middleton, 2019;Modarres & Sadeghi, 2018), and the areas of western Iran, the Khuzestan Plain and the coastal plain of the Persian Gulf in southwestern Iran (the study areas in this research) constitute a regional belt of high-frequency dust outbreaks (Alizadeh-Choobari, Ghafarian, & Owlad, 2016). The high frequency of dust storms in these regions has been attributed to several factors, including low vegetation cover in the arid lands in Iran (Broomandi, Dabir, Bonakdarpour, & Rashidi, 2017a;Esmaili, Tajrishy, & Arasteh, 2006;Najafi et al, 2014), recent droughts in western Iran (Zoljoodi, Didevarasl, & Saadatabadi, 2013), and dust transportation from other regions (e.g., Alizadeh-Choobari et al, 2016;Yu, Notaro, Kalashnikova, & Garay, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Trends in dust storms are variable across the globe, but simulations suggest global annual dust emissions have increased by 25-50% over the last century due to a combination of land use and climate changes [12,15]. Recent trends have shown that dust storm frequency has decreased in some areas (Iran, China, Mauritania), which was attributed to increases in precipitation [16].…”
Section: How Soils Affect Air Quality (A) Direct Source Of Pollutants or Precursors To Pollutants (I) Particulatesmentioning
confidence: 99%